Implantação da logística reversa de lâmpadas fluorescentes no município de Não-Me-Toque/RS: estudo de caso - Valduga, Elisa Tumelero (2015)
This dissertation presents the analysis of reverse logistics fluorescent lamps in the city of Não-Me-Toque, located in the northwest of Rio Grande do Sul. With increased production and consumption of fluorescent lamps since 2001 and also due to discouragement the consumption of incandescent lamps, the generation of hazardous waste is increasing. These products have in their composition dangerous metals such as mercury, which is a heavy metal, toxic to organisms and can bioaccumulate in the food chain. Reverse logistics is an instrument provided for in the Federal Law 12.305/2010 which determines the final destination environmentally suitable fluorescent lamps after consumption through shared responsibility. Thus, this study aimed to examine the reverse logistics of fluorescent lamps in the city of Não-Me-Toque from the point of view of the social actors involved, through interviews and questionnaires. It was observed that 36% of household consumers discard fluorescent lamps with the MSW while 35% return to place of purchase. Only 10% of companies surveyed discard fluorescent lamps with the MSW. Traders and the municipal authorities are organizing to reverse logistics, however, do not have adequate facilities in the storage of collected lamps. Manufacturers, importers and distributors are not adequate. Finally, we proposed a model for reverse logistics fluorescent lamps by centralizing the gathering.